PENGARUH SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL TERHADAP KINERJA KARYAWAN PADA PT SUPER BINTANG SEJAHTERA - Sella, Sella; Putra, Montigor Afrizal (SCIENTIA JOURNAL, 2021)
The company was formed to make a profit, therefore the need for assistance from employee performance. Internal control and accounting information systems are also needed to increase the level of employee performance. This study uses data obtained from the results of questionnaires distributed to company employees as many as 116 respondents. The source of data in this study is primary using non-probability sampling method, the type of saturated sampling method and this research is quantitative. The analysis method uses the SPSS 25 software program. Referring to the results of the T-test in the study, it can be concluded: (1) Accounting Information Systems have an effect on employee performance. 2) Internal control has an effect on employee performance, it is known that the t arithmetic value is 4.311 > t table 1.981 with a significance value of 0.000 < 0.015. The results of the F test where the accounting information system and internal control have a simultaneous effect on employee performance obtained the value of f count 22.209 > 3.08 f table with a significance value of 0.000 < 0.05. So it is stated that simultaneously accounting information system and internal control together have a significant effect on employee performance.